Cooperation and Economic Prosperity: an inter-provincial study in Iran - Hossein Panahi; داود حمیدی رزی; فرهاد عزیزی (تعاون و کشاورزی, 2017)
The aim of this study was to determine the type and size of the effect on selected cooperative sector indicators on the economic growth of various provinces. For this purpose, heteroskedasticity test in panel data-and autocorrelation techniques was utilized.  A Panel Generalized Least Squares (PGLS) estimator was applied. According to the results, the significant positive impact of cooperatives on economic growth among provinces was evaluated and the elasticity of real per capita income to the number of cooperative enterprises 0.10 was estimated. The facilities granted to home-based businesses have a significant and positive impact on the province's economic boom; though had small elasticity (0.02). In contrast, facilities granted to the provinces to expand small and quick return enterprises had insignificant effect on real per capita income of provinces.